Qoraqalpogʻiston florasida zaharli oʻsimliklar va ularnig tarqalishi - Temirbekov, O (SCIENCE and SOCIETY, 2025)
The article describes the total number of species of poisonous plants growing in the flora of the Republic of Karakalpakstan, as well as their distribution in botanical and geographical areas.
Keywords: poisonous plants; wild flora; family; genus; species; chenopodiaceae; brassicaeae; fabaceae; asteraceae; cuscutacea; asclepiadaceae; boraginaceae